2017
DOI: 10.1080/17461391.2017.1301561
|View full text |Cite
|
Sign up to set email alerts
|

3D technology of Sony Bloggie has no advantage in decision‐making of tennis serve direction: A randomized placebo‐controlled study

Abstract: This study aimed at exploring whether 3D technology enhances tennis decision-making under the conceptual framework of human performance model. A 3 (skill-level: varsity, club, recreational) × 3 (experimental condition: placebo, weak 3D [W3D], strong 3D [S3D]) between-participant design was used. Allocated to experimental conditions by a skill-level stratified randomization, 105 tennis players judged tennis serve direction from video scenarios and rated their perceptions of enjoyment, flow, and presence during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…This study revealed that the sports technology investigated should be created to evaluate an athlete's performances. The evaluation of an athlete's performances is important for increasing and developing the performances of athletes [11]. Several studies have found that sports technology can be used to evaluate an athlete's performance.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the sports technology investigated should be created to evaluate an athlete's performances. The evaluation of an athlete's performances is important for increasing and developing the performances of athletes [11]. Several studies have found that sports technology can be used to evaluate an athlete's performance.…”
Section: Discussionmentioning
confidence: 99%